Thermoelectric Energy Harvesting from Vehicle Disc Brake Using SP1848-27145 SA Module: Experimental and Simulation-Based Study - Slamet Khoeron; Rochmad Winarso; Akhmad Zidni Hudaya; Qomaruddin Qomaruddin; Dina Tauhida; Nabil Zakki Nasution (Fakultas Teknik Universitas Muria Kudus, 2026)
The escalating demand for sustainable energy solutions within the automotive industry has catalyzed extensive research into alternative methodologies for energy harvesting. This investigation examines the feasibility of thermoelectric energy harvesting from disc brake systems utilizing the SP1848-27145 SA thermoelectric generator (TEG) module. The selection of the SP1848-27145 SA module is predicated on its dependable electrical output when subjected to moderate temperature differentials characteristic of disc brake operations, in conjunction with its compact and lightweight configuration, which renders it amenable for integration into vehicles.A laboratory-scale apparatus emulating a disc brake system was constructed, and a series of experimental tests alongside computational simulations were conducted to assess the efficiency of the conversion from thermal to electrical energy. Braking loads ranging from 1.5 to 2.25 kg were exerted over intervals of 50 seconds, resulting in disc temperatures ascending to 114.8 Â°C. The maximum output voltage recorded was 0.57 V. Numerical simulations executed with ANSYS 19.2 corroborated the experimental findings, exhibiting a deviation of less than 1%. The maximum power output realized was 185.4 mW under optimal conditions, with a conversion efficiency fluctuating between 4% and 6%.These results underscore the potential applicability of TEGs in facilitating micro-energy systems within the automotive sector. Furthermore, the findings suggest that enhancements in thermal interfaces and optimized cooling techniques could enable this configuration to function as a sustainable auxiliary energy recovery system for hybrid and electric vehicles.